Integrated optical Mach-Zehnder interferometer for biosensor application - Khor, Kang Nan (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2015)
The aim of this study is to develop a dengue RDT that not only have the characteristics of point-of-care (POC) diagnostic but it must also suit the criteria needed to achieve large scale disease surveillance in most developing countries where resource are limited.